Planning of Production, Inventory and Logistics with Direct Shipment and Milk run Strategies: Numerical Experiment - Suebsangin, Pacharawan (Journal of Social and Development Sciences, 2013)
We study a supply chain comprised of a manufacturer owning multiple production lines and a warehouse, and multiple retailers buying from the manufacturer. The manufacturer can choose whether to send products to the retailers directly from loading area using direct shipment or send the product to be stored at the warehouse. If the demand is satisfied from the warehouse, the company can choose the logistic strategy. The company can send the product from the warehouse to a retailer using a direct shipment mode (a truck only visits the retailer) or using milk run mode (a truck visits multiple retailers in a single trip). We develop a mixed integer programming model to find the optimal decisions for production quantities at each production line, the quantities of inventories at the loading area, the warehouse and the retailers, and the transportation strategies to deliver products to retailers in every period. We conduct numerical experiments and then analyze the results. Many managerial insights are drawn for practitioners. Several optimal transportation strategies are observed by mixing between a temporal demand aggregation strategy, the milk run strategy and the direct shipment strategy.